2022
DOI: 10.1021/acs.jpclett.2c00157
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Energy-Dependent Photoluminescence Quantum Yield is Inherent to Optically Robust Core/Alloy-Shell Quantum Dots in a Vast Energy Landscape

Abstract: The importance of alloy-shelling in optically robust Core/Alloy-Shell (CAS) QDs has been described from structural and energetic aspects. Unlike fluorescent dyes, both Core/Shell (CS) and CAS QDs exhibit excitation-energy-dependent photoluminescence quantum yield (PLQY). For both CdSe and InP CAS QDs (with metal- and nonmetal-based alloy-shelling, respectively), with increasing excitation energy, (a) the ultrafast rise-time or relaxation-time to the band-edge increases and (b) the magnitude of the normalized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 100 publications
0
28
0
Order By: Relevance
“…ON and OFF Event Truncation Times . Truncation time for ON event duration (τ C,ON ) is greater than the same for OFF events (τ C,OFF ) (Table and Figure a) indicating a higher value of electron detrapping/trapping rate. ,,, …”
mentioning
confidence: 94%
See 3 more Smart Citations
“…ON and OFF Event Truncation Times . Truncation time for ON event duration (τ C,ON ) is greater than the same for OFF events (τ C,OFF ) (Table and Figure a) indicating a higher value of electron detrapping/trapping rate. ,,, …”
mentioning
confidence: 94%
“…Semiconductor quantum dots (QDs) have mostly been investigated from electron trapping–detrapping points of view toward identifying their suitability for several applications. In CdSe QDs, owing to the presence of suitable energy levels, intrinsic (i.e., without adding any external hole trapping material) hole-trapping phenomenon could be investigated, but such measurements could not be performed for other QDs. However, employing ultrasensitive single-particle spectroscopy (SPS) techniques, intrinsic hole-trapping dynamics could be investigated in CdSe and InP QD systems. , Thus, ultrasensitive SPS has been considered as a highly suitable technique to study the intrinsic hole-trapping dynamics. The extent of intrinsic hole-trapping phenomenon in CdSe and InP QDs has been reported to be quite minimal (less than 10%) from SPS measurement. , Unlike detrimental electron trapping, the intrinsic hole-trapping phenomenon could be beneficial for increasing PLQY. ,,, However, no such report exists in the literature where the significant extent of intrinsic hole trapping or its amplitude variation have been observed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Bisquert and co-workers and Bhattacharyya and co-workers have independently demonstrated that even after encapsulating the core QDs with a higher band gap material or alloying it, the PCE has been found to be low. Therefore, it suggests that engineering of QD cores alone is not sufficient for enhancing the PCE; rather, surface passivation of QDs plays an important role therein. , In this regard, one important fact that needs to be kept in mind is that as QDs do not behave like molecules, , the mechanism of fluorescence response (enhancing or quenching) of QDs in the presence of an analyte may not necessarily follow the same path as is usually followed in the case of molecular dye–analyte interaction events. Although this aspect has been noticed before, enough attention has not been paid.…”
Section: Introductionmentioning
confidence: 99%